Prevalence and predictors of Helicobacter pylori infection in patients with dyspepsia and their association with treatment outcome - Stjepanović, Aleksandra (Medicinski podmladak, 2026)
AbstractIntroduction:  Helicobacter pylori (H. pylori) infection is one of the most common infectious diseases and an established risk factor for gastric cancer. Alongside dyspepsia, it represents a rising global medical burden. Treatment failure of H. pylori infection eradication imposed an imperative to determine risk factors and potential predictors that can be related to its prevalence and  treatment outcome.Aim: Our aim was to assess the prevalence and potential predictors of H. pylori infection in patients with dyspepsia, most prescribed treatment regimens and their effectiveness.Material and methods: A retrospective study including 324 patients with dyspeptic symptoms, who presented at the gastroenterology outpatient unit of the University Clinical Center of Serbia, was conducted. H. pylori diagnosis was made following upper endoscopy and histology. Socio-epidemiologic, clinical and laboratory data was analyzed.Results: The overall prevalence of H. pylori infection in dyspeptic patients was 19.7%. Hematological comorbidities were found to be more common in H. pylori positive patients as compared to the overall sample (15.6% vs 8.1 %, p
Keywords: Helicobacter pylori; dyspepsia; infection treatment